Exploring 3D printing : reflections on four futures of an emerging technology - Kwazema, Martins (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
3D printing as a disruptive additive manufacturing technique requires sufficient navigation around the uncertainty on its possible, probable and preferable socio-technological impacts on society. As a result, it is imperative to design anticipatory systems in order to acquire foresight with respect to the different roadmaps which the technology’s development could assume as it evolves over time. Consequently, the thesis attempts to answers two research questions. The first being "What is the present state of the art of 3D printing in society?". It further attempts to provide answers to the second question which is "What are the opportunities and threats for society in 2030 from 3D printing?". The answers to these questions are presented firstly by articulating discussions on the state of the art as well as the present developments shaping the roles and the future potentials of 3D printing prior to advancing into critical discussions and analyses of the future of the technology in 2030. With respect to the anticipatory efforts required to counter the shocks which might erupt from 3D printing in society, this master’s thesis combines the use of interpretivism as a methodology of choice and the PESTEC table in efforts to carry out a detailed analysis of the inter-relationships between trends, megatrends, driving forces, weak-signals and possible wild-cards which might shape the future of 3D printing. Conclusively, the results of this master’s thesis are presented as an aggregated list of identified future images categorized according to the PESTEC dimensions and four narrative future images for 3D printing in 2030 namely continuous growth, collapse, discipline society and transformation society.